Effects of N-(2-propylpentanoyl) urea on impairment of learning memory and neuronal cell death after bilateral common carotic arteries occlusion in mice - Oraphan Wanakhachornkrai (Chulalongkorn University, 2009)
Thesis (M.Sc.)--Chulalongkorn University, 2006